Análise histomorfométrica do reparo ósseo em tíbias de ratos castrados submetidos ao efeito do alendronato sódico - Vicente Neto, Pedro [UNESP]; Preccaro, Camila Aparecida [UNESP]; Balducci, Eleny Zanella [UNESP] (My University, 2010)
This study used histomorphometric analysis to investigate the effect of sodium alendronate, used for the treatment of osteoporosis, on the repair of surgically-induced bone defects in the tibia of castrated rats. Methods: The castrated animals were given subcutaneous injections of sodium alendronate (0.7mg/Kg) diluted in saline once a week; the control animals were given the same dose of saline. At 16, 30 and 44 days after the first injection of sodium alendronate, the animals were sacrificed and the right tibias were removed and processed for histomorphometric analysis. The volumetric bone mineral density was estimated by a reticular grid (25 points) attached to a light microscope. The number of points on the bone tissue was counted in the histological sections, totaling 100 points/animal. Results: The results revealed that sodium alendronate stimulated bone formation in castrated rats in all occasions, mainly at 16 and 30 days. Conclusion: Sodium alendronate affects mineral homeostasis, promoting bone repair.

Avaliar por meio da análise histomorfométrica o efeito do alendronato sódico, utilizado para tratamento da osteoporose, na reparação óssea em defeitos previamente confeccionados em tíbias direitas de ratos submetidos à castração. Métodos: Os ratos tratados receberam, uma vez por semana, injeção subcutânea de alendronato sódico diluído em solução salina na dose de 0,7mg/kg e os controles, a mesma dose de salina. Aos 16, 30 e 44 dias após a aplicação da primeira dose do alendronato sódico, os animais foram sacrificados, as tíbias direitas removidas e processadas para análise histomorfométrica. A densidade volumétrica foi estimada por um método de contagem diferencial de pontos, em imagens histológicas analisadas ao microscópio munido de uma ocular (10X) contendo um retículo com 25 pontos equidistantes totalizando 100 pontos para cada animal analisado. Resultados: A análise demonstrou que a administração do alendronato sódico, em ratos castrados, estimulou a formação de tecido ósseo, em todos os períodos observados, sendo mais significante, nos períodos de 16 e 30 dias. Conclusão: O alendronato sódico interferiu na homeostasia mineral, favorecendo o reparo ósseo
Histomorphometric analysis of bone repair in tibias of castrated rats submitted to the effects of sodium alendronate
Keywords: Alendronate; Bone regeneration; Rats; Alendronato; Ratos; Regeneração óssea